American Civil Liberties Union Forum at Unitarian Universalist Church - Watkins, Howard::::::::: (1986)
Hague Foster, Carol Penn,, Sam Gitchel, Dorothy Ehrlich, Nadia Coleman and Howard Watkins in front of American Civil Liberties Union banner